Correction: Predictors associated with successful weaning of veno-venous extracorporeal membrane oxygenation and mortality in adult patients with severe acute lung failure: Protocol of a pooled data analysis of cohort studies. - PLOS One Staff (PLoS ONE)
[This corrects the article DOI: 10.1371/journal.pone.0303282.].